2022
DOI: 10.3390/ijms23073754
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 Serves as a Biomarker for Poor Prognosis in Breast Carcinoma

Abstract: BRCA1/2 are breast cancer susceptibility genes that are involved in DNA repair and transcriptional control. They are dysregulated in breast cancer, making them attractive therapeutic targets. Here, we performed a systematic multiomics analysis to expound BRCA1/2 functions as prognostic biomarkers in breast cancer. First, using different web-based bioinformatics platforms (Oncomine, TIMER 2.0, UALCAN, and cBioportal), the expression of BRCA1/2 was assessed. Then, the R package was used to analyze the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Approximately 20% of breast cancer tumors show an amplification of the BRCA1 gene [ 1 ]. Increased expression of BRCA1 was associated with inferior patient survival after therapy [ 3 ]. The cause of therapy resistance may be due to the requirement of BRCA1 for efficient DSB repair or superior protection of the DNA replication forks [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20% of breast cancer tumors show an amplification of the BRCA1 gene [ 1 ]. Increased expression of BRCA1 was associated with inferior patient survival after therapy [ 3 ]. The cause of therapy resistance may be due to the requirement of BRCA1 for efficient DSB repair or superior protection of the DNA replication forks [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…BRCA1 and BRCA2 are the most mutated genes in breast cancer [ 1 , 2 ]. For BRCA1 it was shown that not only a loss but also an amplification of the gene, leading to increased protein expression, result in an adverse prognosis for patient survival due to therapy resistance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In T2WI, images are obtained after a long repetition time and a long echo scan, which is mainly composed of images of intracellular, extracellular and extravascular space, and clearly show the morphology of the tumor ( 25 ). T2WI images are helpful for the diagnosis of breast cancer and molecular typing.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1/2 has received a lot of interest recently as a biomarker for predicting cancer prognosis. The discovery of biomarkers such as BRCA1/2 is critical in advancing the precise therapy of triple-negative breast cancer (TNBC) [ 74 ]. In a similar study, an HRP-mimic DNAzyme CL amplified platform was provided to detect BRCA1.…”
Section: Dnazymes-assisted Aptasensors For Cancer Detectionmentioning
confidence: 99%